CONDITIONS FOR INTUITIVE DECISION MAKING: THE CHINESE EXECUTIVES IN THAILAND - Klungsoontornrangsi, Kreingkrai (2007)
Do Thai-Chinese managers have the ability required for their organizations to survive in an information-void environment of Thailand? How much they rely on intuition in facilitating the process of business decision making? A study of eight managers provides new insights to these questions.